A Novel Method for Assessing Respiratory Deposition of Welding Fume Nanoparticles - Cena, L. G. (J Occup Environ Hyg, 2014)
Welders are exposed to high concentrations of nanoparticles. Compared to larger particles, nanoparticles have been associated with more toxic effects at the cellular level, including the generation of more reactive oxygen species activity. Current methods for welding-fume aerosol exposures do not differentiate between the nano-fraction and the larger particles. The objectives of this work are to establish a method to estimate the respiratory deposition of the nano-fraction of selected metals in welding fumes and test this method in a laboratory setting. Manganese (Mn), Nickel (Ni), Chromium (Cr), and hexavalent chromium (Cr(VI)) are commonly found in welding fume aerosols and have been linked with severe adverse health outcomes. Inductively coupled plasma mass spectrometry (ICP-MS) and ion chromatography (IC) were evaluated as methods for analyzing the content of Mn, Ni, Cr, and Cr(VI) nanoparticles in welding fumes collected with nanoparticle respiratory deposition (NRD) samplers. NRD samplers collect nanoparticles at deposition efficiencies that closely resemble physiological deposition in the respiratory tract. The limits of detection (LODs) and quantitation (LOQs) for ICP-MS and IC were determined analytically. Mild and stainless steel welding fumes generated with a robotic welder were collected with NRD samplers inside a chamber. LODs (LOQs) for Mn, Ni, Cr, and Cr(VI) were 1.3 μg (4.43 μg), 0.4 μg (1.14 μg), 1.1 μg (3.33 μg), and 0.4 μg (1.42 μg), respectively. Recovery of spiked samples and certified welding fume reference material was greater than 95%. When testing the method, the average percentage of total mass concentrations collected by the NRD samplers was ~30% for Mn, ~50% for Cr, and ~60% for Ni, indicating that a large fraction of the metals may lie in the nanoparticle fraction. This knowledge is critical to the development of toxicological studies aimed at finding links between exposure to welding fume nanoparticles and adverse health effects. Future work will involve the validation of the method in workplace settings. [Supplementary materials are available for this article. Go to the publisher’s online edition of Journal of Occupational and Environmental Hygiene for the following free supplemental resource: Digestion, extraction, and analysis procedures for nylon mesh screens.]